Hantavirus Regulation of Type I Interferon Responses - Valery Matthys; Erich R. Mackow (Advances in Virology)
Hantaviruses primarily infect human endothelial cells (ECs) and cause two highly lethal human diseases. Early addition of Type I interferon (IFN) to ECs blocks hantavirus replication and thus for hantaviruses to be pathogenic they need to prevent early interferon induction. PHV replication is blocked in human ECs, but not inhibited in IFN deficient VeroE6 cells and consistent with this, infecting ECs with PHV results in the early induction of IFNβ and an array of interferon stimulated genes (ISGs). In contrast, ANDV, HTNV, NY-1V and TULV hantaviruses, inhibit early ISG induction and successfully replicate within human ECs. Hantavirus inhibition of IFN responses has been attributed to several viral proteins including regulation by the Gn proteins cytoplasmic tail (Gn-T). The Gn-T interferes with the formation of STING-TBK1-TRAF3 complexes required for IRF3 activation and IFN induction, while the PHV Gn-T fails to alter this complex or regulate IFN induction. These findings indicate that interfering with early IFN induction is necessary for hantaviruses to replicate in human ECs, and suggest that additional determinants are required for hantaviruses to be pathogenic. The mechanism by which Gn-Ts disrupt IFN signaling is likely to reveal potential therapeutic interventions and suggest protein targets for attenuating hantaviruses.